Urea-melt solubilization of single-walled carbon nanotubes - Ford, William; Jung, Adrian; Hirsch, Andreas; Graupner, Ralf; Scholz, Frank; Yasuda, Akio; Wessels, Jurina (Advanced Materials, 2006)
A new method for urea-melt solubilizing acid-purified single-walled carbon nanotubes, is presented. The urea-modified single-walled carbon nanotubes (U-SWNTs) were isolated from the extracts by precipitation with sodium perchlorate and redissolved in water after the removal of excess sodium perchlorate by washing. The optimal reaction temperature for the urea-melt process was determined to be around 150°C, and differential scanning calorimetric measurements indicated that the reaction occurred rapidly when the temperature reached 140°C. This process is quick, environmental-friendly, provides full-length SWNTs with excellent water solubility.